2005
DOI: 10.1159/000085930
|View full text |Cite
|
Sign up to set email alerts
|

Penile Sensitivity and Sexual Satisfaction after Circumcision: Are We Informing Men Correctly?

Abstract: Objectives: Currently no consensus exists about the role of the foreskin or the effect circumcision has on penile sensitivity and overall sexual satisfaction. Our study assesses the effect of circumcision on sexually active men and the relative impact this may have on informed consent prior to surgery. Materials and Methods: One hundred and fifty men between the ages of 18 and 60 years were identified as being circumcised for benign disease between 1999 and 2002. Patients with erectile dysfunction were exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 32 publications
1
68
1
1
Order By: Relevance
“…Conversely, Masood et al 28 reported a 38% improvement in penile sensation after circumcision. An overall 61% satisfaction rate was considered as a poor outcome of circumcision.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, Masood et al 28 reported a 38% improvement in penile sensation after circumcision. An overall 61% satisfaction rate was considered as a poor outcome of circumcision.…”
Section: Discussionmentioning
confidence: 96%
“…12,13,28 The relatively short, post-circumcision follow-up period may not accurately reflect sexual function at a later time, resulting in risk of bias for this meta-analysis. 26,28,29 Furthermore, the study validity may be affected by several factors, including subjective selfreporting, lack of physiological or laboratory indicators of sexual dysfunction or consensus on what constitutes sexual dysfunction for individuals with different education levels, cultures and religions. Moreover, operative methods, participants' ages and any coexisting medical conditions were not analysed by subgroup, and these could also contribute to study bias.…”
Section: Discussionmentioning
confidence: 99%
“…(118,119) Erectile function scores were unchanged after circumcision of adult men. (120) And intravaginal latency times were no different (6.7 versus 6.0 min in circumcised versus uncircumcised men, respectively) in a study of 500 couples in the USA, UK, Netherlands, Spain and Turkey.…”
Section: Cervical Cancermentioning
confidence: 90%
“…(122) Women's preference for the circumcised penis for sexual activity, appearance and hygiene is one reason. (120,122,123) Males in higher socio-economic-educational categories in the USA, UK and Australia have higher rates of circumcision. (10,122,123) Circumcision methods Various devices are used to protect the penis during excision of the prepuce in infants.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Some international epidemiologic studies demonstrated lower prevalence for PE in Middle East, confirming this presumption (36). However, clinical studies regarding the penile sensitivity, PE status and sexual satisfaction report conflicting results are not conclusive (11,(141)(142)(143)(144)(145).…”
Section: Circumcision and Pementioning
confidence: 97%